2003
DOI: 10.1037/0022-3514.84.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Preference-consistent evaluation of information in the hidden profile paradigm: Beyond group-level explanations for the dominance of shared information in group decisions.

Abstract: Common explanations for the failure of groups to solve so-called hidden profiles focus on group processes, namely insufficient discussion of unshared information and premature consensus on a suboptimal alternative. As 2 experiments show, even in the absence of such group processes, hidden profiles are hardly ever solved. In Experiment 1, participants first received individual information about a personnel selection task and then read a group discussion protocol containing full information exchange. If the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
199
1
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 237 publications
(219 citation statements)
references
References 55 publications
11
199
1
8
Order By: Relevance
“…The findings of our study also tie in with results from Greitemeyer and Schulz-Hardt (2003) who found that individuals tend to stick to their initial decision because they judge preference-consistent information to be more compelling than preference-inconsistent information. In our opinion, the processes outlined in the two studies complement each other.…”
Section: Theoretical Implicationssupporting
confidence: 87%
See 3 more Smart Citations
“…The findings of our study also tie in with results from Greitemeyer and Schulz-Hardt (2003) who found that individuals tend to stick to their initial decision because they judge preference-consistent information to be more compelling than preference-inconsistent information. In our opinion, the processes outlined in the two studies complement each other.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…Kerschreiter, Schulz-Hardt, Faulmüller, Mojzisch, & Frey, 2008). Thus, instead of showing effects of social validation, the results of these studies might be due to the fact that individuals evaluate preference-consistent information more favorably than preference-inconsistent information and, hence, accord less weight to preference-inconsistent information -a causal chain that has been shown by Greitemeyer and Schulz-Hardt (2003).…”
Section: Empirical Support For the Social Validation Hypothesismentioning
confidence: 87%
See 2 more Smart Citations
“…Se ha encontrado que estos se centran en analizar y sopesar sus acciones con base en la información compartida a expensas de la información no compartida, lo que puede potenciar o hacer decaer su rendimiento de acuerdo con el tipo de información (Greitemeyer & Schulz-Hardt, 2003;Kameda, Takezawa, Tindale & Smith, 2002).…”
Section: Cognición Grupal Humana Y Toma De Decisionesunclassified